(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The present report has been conducted in Bhandara District ,of Maharashtra . Bhandara is well known for its natural diverse Flora and Fauna .Bhandara covered the area about 3,717 square kilometre .The natural vegetation of this District includes the most of the plant species of medicinal and nutritional importance, which were regularly being used by the tribal peoples to cure various diseases and for nutritional objectives .The paper includes important nutritional medicinal plants, which is under endangered and threatened categories.